2022
DOI: 10.3390/antibiotics11020176
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Use in Hospitalised Patients with COVID-19: An International Multicentre Point-Prevalence Study

Abstract: Studies suggest that the incidence of coinfections in patients with the coronavirus disease 2019 (COVID-19) is low, but a large number of patients receive antimicrobials during hospitalisation. This may fuel a rise in antimicrobial resistance (AMR). We conducted a multicentre point-prevalence survey in seven tertiary university hospitals (in medical wards and intensive care units) in Croatia, Italy, Serbia and Slovenia. Of 988 COVID-19 patients, 521 were receiving antibiotics and/or antifungals (52.7%; range a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…Our meta-analysis included nine el-igible studies in the field plus the current study (total of ten studies) (23)(24)(25)(26)(27)(28)(29)(30)(31) after an electronic search and removing duplicate and irrelevant records. The distribution of each survey by country is as follows: Spain, USA, Iran, Saudi Arabia, UK, Italy, a multicenter study from Italy, Croatia, Serbia, Slovenia, and two studies from Turkey.…”
Section: Meta-analysismentioning
confidence: 99%
“…Our meta-analysis included nine el-igible studies in the field plus the current study (total of ten studies) (23)(24)(25)(26)(27)(28)(29)(30)(31) after an electronic search and removing duplicate and irrelevant records. The distribution of each survey by country is as follows: Spain, USA, Iran, Saudi Arabia, UK, Italy, a multicenter study from Italy, Croatia, Serbia, Slovenia, and two studies from Turkey.…”
Section: Meta-analysismentioning
confidence: 99%
“…Targeted therapy according to bacterial culture and sensitivity testing was highest in AICU (4.9%, n = 2/41) non-significantly (Table S5). Similarly, was highest in ICU (47%) in another PPS [43] . Based on our results, targeted therapy is deficient if it exists primarily prescribed in AICU where more resistant pathogens available needs a C/S test [44] .…”
Section: Resultsmentioning
confidence: 83%
“…Previous data suggest that 65% of children with COVID-19 have some type of respiratory symptoms, about one half have fever, and 38% have coughing [ 8 ], while many fewer children present gastrointestinal symptoms. We observed that cough and fever were the most common symptoms of children hospitalized with COVID-19 in our institution, which is not surprising, as they were most commonly found as the symptoms of COVID-19 pneumonia in children [ 39 ]. Outside of the hospital, however, a large-scale study of children with COVID-19 from the UK found that headache, fatigue, and anosmia were the most common symptoms [ 32 ].…”
Section: Discussionmentioning
confidence: 91%